Visit of Prime Minister Dr. Manmohan Singh to Germany & Uzbekistan, 22 to 26 April 2006. - Manmohan Singh 1932- (Public Diplomacy Division, Ministry of External Affairs, Government of India, 2006)
Selected speeches of Prime Minister of India during his visit to Germany and Uzbekistan in April 2006.